Question
upstudy study bank question image url

Q2: Find \( \frac{\partial f}{\partial x} \) and \( \frac{\partial f}{\partial y} \) of the following functions: (a) \( f(x, y)=\left(x^{2}-1\right)(3 y+5) \) (b) \( f(x, y)=y^{2}-y \sin (x y)+x^{3}-1 \)

Ask by Adkins Carlson. in Egypt
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

For function (a): \[ \frac{\partial f}{\partial x} = 6xy + 10x \] \[ \frac{\partial f}{\partial y} = 3x^{2} - 3 \] For function (b): \[ \frac{\partial f}{\partial x} = -y^{2} \cos(xy) + 3x^{2} \] \[ \frac{\partial f}{\partial y} = 2y - \sin(xy) - xy \cos(xy) \]

Solution

Alright, I need to find the partial derivatives of the given functions with respect to \( x \) and \( y \). Let's tackle them one by one. **Function (a):** \( f(x, y) = (x^{2} - 1)(3y + 5) \) First, I'll expand the function to simplify the differentiation process. Multiplying the terms inside the parentheses: \[ f(x, y) = (x^{2} - 1)(3y + 5) = 3x^{2}y + 5x^{2} - 3y - 5 \] Now, I'll find the partial derivatives. 1. **Partial derivative with respect to \( x \):** \[ \frac{\partial f}{\partial x} = \frac{\partial}{\partial x}(3x^{2}y) + \frac{\partial}{\partial x}(5x^{2}) + \frac{\partial}{\partial x}(-3y) + \frac{\partial}{\partial x}(-5) \] Calculating each term: - \( \frac{\partial}{\partial x}(3x^{2}y) = 6xy \) - \( \frac{\partial}{\partial x}(5x^{2}) = 10x \) - \( \frac{\partial}{\partial x}(-3y) = 0 \) (since \( y \) is treated as a constant) - \( \frac{\partial}{\partial x}(-5) = 0 \) (constant term) So, \[ \frac{\partial f}{\partial x} = 6xy + 10x \] 2. **Partial derivative with respect to \( y \):** \[ \frac{\partial f}{\partial y} = \frac{\partial}{\partial y}(3x^{2}y) + \frac{\partial}{\partial y}(5x^{2}) + \frac{\partial}{\partial y}(-3y) + \frac{\partial}{\partial y}(-5) \] Calculating each term: - \( \frac{\partial}{\partial y}(3x^{2}y) = 3x^{2} \) - \( \frac{\partial}{\partial y}(5x^{2}) = 0 \) (since \( x^{2} \) is treated as a constant) - \( \frac{\partial}{\partial y}(-3y) = -3 \) - \( \frac{\partial}{\partial y}(-5) = 0 \) (constant term) So, \[ \frac{\partial f}{\partial y} = 3x^{2} - 3 \] **Function (b):** \( f(x, y) = y^{2} - y \sin(xy) + x^{3} - 1 \) This function involves a product of \( y \) and \( \sin(xy) \), so I'll need to use the product rule for differentiation. 1. **Partial derivative with respect to \( x \):** \[ \frac{\partial f}{\partial x} = \frac{\partial}{\partial x}(y^{2}) - \frac{\partial}{\partial x}(y \sin(xy)) + \frac{\partial}{\partial x}(x^{3}) - \frac{\partial}{\partial x}(1) \] Calculating each term: - \( \frac{\partial}{\partial x}(y^{2}) = 0 \) (since \( y^{2} \) is treated as a constant) - \( \frac{\partial}{\partial x}(y \sin(xy)) = y \cos(xy) \cdot \frac{\partial}{\partial x}(xy) = y \cos(xy) \cdot y = y^{2} \cos(xy) \) - \( \frac{\partial}{\partial x}(x^{3}) = 3x^{2} \) - \( \frac{\partial}{\partial x}(1) = 0 \) (constant term) So, \[ \frac{\partial f}{\partial x} = -y^{2} \cos(xy) + 3x^{2} \] 2. **Partial derivative with respect to \( y \):** \[ \frac{\partial f}{\partial y} = \frac{\partial}{\partial y}(y^{2}) - \frac{\partial}{\partial y}(y \sin(xy)) + \frac{\partial}{\partial y}(x^{3}) - \frac{\partial}{\partial y}(1) \] Calculating each term: - \( \frac{\partial}{\partial y}(y^{2}) = 2y \) - \( \frac{\partial}{\partial y}(y \sin(xy)) = \sin(xy) + y \cos(xy) \cdot \frac{\partial}{\partial y}(xy) = \sin(xy) + y \cos(xy) \cdot x = \sin(xy) + xy \cos(xy) \) - \( \frac{\partial}{\partial y}(x^{3}) = 0 \) (since \( x^{3} \) is treated as a constant) - \( \frac{\partial}{\partial y}(1) = 0 \) (constant term) So, \[ \frac{\partial f}{\partial y} = 2y - \sin(xy) - xy \cos(xy) \] **Summary:** - For function (a): - \( \frac{\partial f}{\partial x} = 6xy + 10x \) - \( \frac{\partial f}{\partial y} = 3x^{2} - 3 \) - For function (b): - \( \frac{\partial f}{\partial x} = -y^{2} \cos(xy) + 3x^{2} \) - \( \frac{\partial f}{\partial y} = 2y - \sin(xy) - xy \cos(xy) \)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To find the partial derivatives of the given functions, we will differentiate with respect to \( x \) and \( y \) while treating the other variable as a constant. For part (a): 1. To find \( \frac{\partial f}{\partial x} \): \[ \frac{\partial f}{\partial x} = \frac{\partial}{\partial x}\left((x^{2}-1)(3y+5)\right) = (2x)(3y+5) + (x^{2}-1)(0) = 2x(3y+5) = 6xy + 10x \] 2. To find \( \frac{\partial f}{\partial y} \): \[ \frac{\partial f}{\partial y} = \frac{\partial}{\partial y}\left((x^{2}-1)(3y+5)\right) = (x^{2}-1)(3) = 3(x^{2}-1) \] So the answers for part (a): - \( \frac{\partial f}{\partial x} = 6xy + 10x \) - \( \frac{\partial f}{\partial y} = 3(x^{2}-1) \) For part (b): 1. To find \( \frac{\partial f}{\partial x} \): \[ \frac{\partial f}{\partial x} = \frac{\partial}{\partial x}\left(y^{2} - y \sin (xy) + x^{3} - 1\right) = 0 - y \cos(xy) \cdot y + 3x^{2} - 0 = 3x^{2} - y^{2} \cos(xy) \] 2. To find \( \frac{\partial f}{\partial y} \): \[ \frac{\partial f}{\partial y} = \frac{\partial}{\partial y}\left( y^{2} - y \sin(xy) + x^{3} - 1\right) = 2y - \left(\sin(xy) + xy \cos(xy)\right) + 0 - 0 = 2y - \sin(xy) - xy \cos(xy) \] Therefore, the results for part (b): - \( \frac{\partial f}{\partial x} = 3x^{2} - y^{2} \cos(xy) \) - \( \frac{\partial f}{\partial y} = 2y - \sin(xy) - xy \cos(xy) \)

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy